أهمية قياس الشخصية في علم النفس وبعض المشكلات المؤثرة فيه - مهداوي, سامية; ركزة, سميرة; مهلل, زينة (جامعة الوادي University of Eloued, 2016)
هدفت الدراسة الحالية إلى معرفة أهمية قياس الشخصية في علم النفس، وكذا معرفة بعض المشكلات التي تظهر في مقاييس الشخصية، لأن الهدف الذي يسعى إليه القياس النفسي بصفة عامة وقياس الشخصية بصفة خاصة هو الوصول إلى أكبر قدر من الدقة في المواضيع التي يتناولها علم النفس، قصد معرفة العلاقات القائمة بين أجزاء الظواهر النفسية ومحاولة ضبطها والتحكم فيها، وهو ما يتيح للباحثين أو السيكولوجيين فهم ظاهرة معينة بشكل دقيق ومحدد، وتعتبر الشخصية من المواضيع التي تتأثر بعدة عوامل عند قياسها، وهو ما يجب الانتباه إليه من طرف الباحثين إضافة إلى طرق استجابة الأفراد لمقاييس الشخصية التي تتخللها عدة مشكلات، لأن الأخذ هذه الأمور بعين الاعتبار يؤدي إلى عملية قياس أكثر دقة وموضوعية. The purpose of this study was to investigate the importance of personality measurement in psychology, as well as identification of some of problems that appear in the personality scales because the aim sought by Psychometrics in general and personality measurement, in particular, is to reach a greater degree of accuracy in the subjects covered by psychology in order to find out relations between psychological phenomena parts and try to adjust and control them, which allows researchers or psychologists to understand a particular phenomenon accurately and specifically. Personality is one of the subjects that are affected by several factors when measured, which requires a special attention by researchers. In addition to ways of individuals' responses to personality scales which contain several problems, because taking these things into consideration leads to a more accurate and objective
مقال
Keywords: تشويه الاستجابة، الصدق والثبات; Personality, distortion of response, validity and reliability